Pengaruh game based learning terhadap kemampuan problem solving pada operasi hitung campuran peserta didik kelas IV sekolah dasar - Aisyah Qurrota A'yun; Karsono Karsono (Didaktika Dwija Indria, 2025)
The purpose of this study is to ascertain how game-based learning affects fourth-grade students' problem-solving skills in mixed arithmetic operations. Pre-experimental design with a single group pretest-posttest form is the research approach employed; that is, a design in which observations are made twice: once before treatment (pre-test) and once after treatment (post-test). Prerequisite and hypothesis tests are two types of data analysis approaches. The Nusukan State Elementary School served as the site of the study. The study's sample consisted of 21 pupils from class IV, and it was conducted during the odd semester of the 2024/2025 academic year. Descriptive data were derived from the pretest results, which had an average score of 38.05, and the post-test findings, which had an average score of 82.67. H0 was rejected while Ha was approved based on the Wilcoxon signed rank test results, which showed a significance of 0.000 <0.05. The researcher can therefore draw the conclusion that game-based learning has a major impact on fourth-grade students at Nusukan State Elementary School's capacity for problem-solving.